2022
DOI: 10.1177/13505084221119267
|View full text |Cite
|
Sign up to set email alerts
|

In praise of boredom at work

Abstract: In the context of management and organisational literature, boredom has largely been seen in individual, psychological and negative terms, both for those experiencing it and for organisational outcomes. Through selective references to a wider sociological, historical and philosophical set of perspectives, we make a case here for refiguring boredom at work as a more relational and political notion. Rather than being seen as negative or trivial, we suggest that it is central to the concerns of organisation studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The response of workers to threatening forms of control has been found to be diverse, ranging from compliance to covert and, ultimately, overt forms of resistance. For example, to maintain their identities, they may collectively display a gesture of compliance while deploying such tactics as cynicism, irony, foot dragging, boredom, staged performance, or reinvention of meaning (Fleming & Spicer, 2008; Noury et al, 2022; Siltaloppi et al, 2022; Ybema & Horvers, 2017). Ultimately, any movement towards the practices entailed in resistance appears to arise from contradictions between the attempts by management to define an organizational identity and the corresponding response of workers who maintain their own sense of personal and collective meaning.…”
Section: The Collective Nature Of Work and Learningmentioning
confidence: 99%
“…The response of workers to threatening forms of control has been found to be diverse, ranging from compliance to covert and, ultimately, overt forms of resistance. For example, to maintain their identities, they may collectively display a gesture of compliance while deploying such tactics as cynicism, irony, foot dragging, boredom, staged performance, or reinvention of meaning (Fleming & Spicer, 2008; Noury et al, 2022; Siltaloppi et al, 2022; Ybema & Horvers, 2017). Ultimately, any movement towards the practices entailed in resistance appears to arise from contradictions between the attempts by management to define an organizational identity and the corresponding response of workers who maintain their own sense of personal and collective meaning.…”
Section: The Collective Nature Of Work and Learningmentioning
confidence: 99%
“…Second, several studies have shown that temporal structures influence the temporal experiences of organizational actors (e.g., Bailey & Suddaby, 2023; Briscoe, 2007; Dorow & Jean, 2022; Katila et al, 2020). Whereas some temporal structures can trigger experiences of flow and timelessness (Mainemelis, 2001), others can result in boredom (Noury, Ahuja, Parker, Sturdy, & Tyler, 2022) or even stress and burnout (e.g., Blagoev & Schreyögg, 2019; Lupu & Rokka, 2022; Perlow, 1999). Some temporal experiences—such as serving time in prison—might point “to a more fundamental and negative dimension of time, where the processual construction of meaningful time is substituted for a radical experience of finitude” (Johnsen, Berg Johansen, & Toyoki, 2019: 15).…”
Section: Time As Structurementioning
confidence: 99%
“…The ‘feeling of powerlessness is closely bound up with boredom’, which ‘is a function of life under the compulsion to work and under the rigorous division of labour. Boredom need not necessarily exist’ (Adorno, 2005a: 171), yet it is perhaps one of the most common workplace experiences (Cederström and Fleming, 2012; Fisher, 1993; Johnsen, 2016; Noury et al, 2022).…”
Section: Adorno’s Critique Of Modern Workmentioning
confidence: 99%